2015
DOI: 10.1111/pim.12216
|View full text |Cite
|
Sign up to set email alerts
|

Immunity and immune modulation elicited by the larval cestode Mesocestoides vogae and its products

Abstract: Larval cestodes (metacestodes) induce long-lasting infections leading to considerable pathology in humans and livestock. Their survival is typically associated with Th2-biased immune responses and immunosuppressive effects and depends on the parasite's ability to excrete/secrete antigens with immunoregulatory properties. Here, Mesocestoides vogae, a natural parasite of mice, is proposed as a new model species for the identification and characterization of cestode-derived immunomodulatory factors. We followed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(45 citation statements)
references
References 44 publications
(75 reference statements)
4
41
0
Order By: Relevance
“…As in the case of helminth infections, M. corti tetrathyridia mediate a chronic disease that is associated with parasite‐induced T helper‐2 (Th2) and tolerogenic immune responses . Research on nematode and trematode systems has demonstrated the importance of DCs in the induction of such immunosuppressive mechanisms .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As in the case of helminth infections, M. corti tetrathyridia mediate a chronic disease that is associated with parasite‐induced T helper‐2 (Th2) and tolerogenic immune responses . Research on nematode and trematode systems has demonstrated the importance of DCs in the induction of such immunosuppressive mechanisms .…”
Section: Discussionmentioning
confidence: 99%
“…Dendritic cells (DCs) exert major functions not only to elicit immune responses but also to regulate immune tolerance. Therefore, DCs are major targets for microbial immune evasion by specifically blocking their IL‐12 production to deviate the immune response to type‐2 immune response as observed for all groups of helminths such as trematodes , nematodes and as shown by us more recently also for cestodes .…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…In the subsequent experiments aimed at studying the direct effect of parasitic ES antigens, groups of mice (n=5) received either intraperitoneal injections of 200 µl of PBS (control) or 20 µg of ES in 200 µl of PBS and the applications of ES and PBS were performed six times, every day for a total of 6 days. The antigen doses correlated approximately with the concentration of M. vogae secretion detected in vivo [4]. In these experiments, peritoneal uid and PEC were isolated as described below and used in further analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Invasion of the hepatic tissue by larvae results in extensive parenchymal destruction with brosis and the development of ascites. To date, the experimental model of larval cestodiasis has been preferentially used to study host-parasite interactions, speci cally in the liver [3] or the peritoneum [4]. Intracranial inoculation of metacestodes serves as a laboratory model of neurocysticercosis to study immunity and metacestodes-associated pathology in the brain [5,6].…”
Section: Introductionmentioning
confidence: 99%